2012
DOI: 10.1080/17429145.2012.693207
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum tolerance measured by root growth and mucilage protection inUrochloa brizanthaandUrochloa decumbens

Abstract: Aluminum toxicity on root systems was analyzed through comparing root growth and evaluating the protective function of mucilage in Urochloa decumbens and Urochloa brizantha. Seedlings were grown in a solution with different concentrations of AlCl 3 and with mucilage removed or present. The root elongation rate, total length, number of roots and presence of aluminum at the root apex were measured. Root development was inhibited by aluminum and the elongation rate was maintained without any difference between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 21 publications
0
5
0
5
Order By: Relevance
“…Similar decreases in root growth in response to aluminium were found in Jatropha curcas (Rosado et al, 2012), sorghum (Too et al, 2014), and barley (Tamas et al, 2006) in studies that used a similar methodology (e.g., measuring the root growth in seedlings in paper rolls moistened with aluminium solutions). Studies using hydroponic (Giannakoula et al, 2010;Arroyave et al, 2011Arroyave et al, , 2013Matins et al, 2011;Ramos et al, 2012;Roselló et al, 2015), semi-hydroponic (Colombo et al, 2016), and even growth in soil methods (Mutimura & Everson, 2012) have found similar results, but these methods are expensive and time consuming. Hare and Cress (1997) reported that proline accumulation occurred when wheat was exposed to water deficits, and therefore was a function of osmotic regulation and cellular protection.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar decreases in root growth in response to aluminium were found in Jatropha curcas (Rosado et al, 2012), sorghum (Too et al, 2014), and barley (Tamas et al, 2006) in studies that used a similar methodology (e.g., measuring the root growth in seedlings in paper rolls moistened with aluminium solutions). Studies using hydroponic (Giannakoula et al, 2010;Arroyave et al, 2011Arroyave et al, , 2013Matins et al, 2011;Ramos et al, 2012;Roselló et al, 2015), semi-hydroponic (Colombo et al, 2016), and even growth in soil methods (Mutimura & Everson, 2012) have found similar results, but these methods are expensive and time consuming. Hare and Cress (1997) reported that proline accumulation occurred when wheat was exposed to water deficits, and therefore was a function of osmotic regulation and cellular protection.…”
Section: Discussionmentioning
confidence: 97%
“…According to Bitencourt et al (2011), Ramos et al (2012, and Arroyave et al (2011;2013), the Basilisk cultivar is the most resistant to poor soils and to free aluminium. Based on the dendrogram made using the phenotypic characters for both assays, it could be seen that the Basilisk cultivar was the most distant cultivar in both dendrograms (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…Os rebanhos bovinos, muitas vezes estão localizados em áreas com solos de baixa fertilidade, ácidos e com altos teores de alumínio trocável (Al 3+ ), limitando o potencial produtivo das plantas e, consequentemente, comprometendo os índices zootécnicos. Na região de Cerrado, principalmente, atribui-se a redução do crescimento das plantas à acidez do solo, ao excesso de Al e baixos teores de fósforo (RAMOS et al, 2012 (EMBRAPA, 2006). Considerada espécie perene, os rizomas apresentam-se em forma de nódulos pequenos.…”
Section: Importância Das Pastagensunclassified
“…O ápice radicular, e particularmente a parte distal da zona de transição, é a região mais sensível ao estresse induzido pelo Al (SIVAGURU;HORST, 1998;KOLLMEIER;FELLE;HORST, 2000;HUANG et al, 2009). O sintoma de toxidez causada por Al é facilmente observado pela inibição do crescimento radicular, encurtamento e o espessamento das pontas radiculares, prejudicando a formação de raízes finas, o que consequentemente reduz a absorção de água e nutrientes pelas plantas (KERRIDGE;DAWSON;MOORE, 1971;FOY, 1976;KOCHIAN, 1995 (BITENCOURT et al, 2011;RAMOS et al, 2012).…”
Section: Alumínio Na Plantaunclassified
See 1 more Smart Citation